Optimizing E-Loyalty on The Bukalapak E-Commerce Platform: Exploring the Role of E-Service Quality Mediated by E-Satisfaction and E-Trust - Apriyanti, Nina; Azizah, Siti Ijah; Maulany, Soesanty (International Journal of Business, Economics, and Social Development, 2024)
This study aims to analyze and prove the effect of e-service quality on optimizing e-loyalty mediated by e-trust and e-satisfaction on the Bukalapak e-commerce platform by focusing on Bukalapak users in Cirebon City. This research focuses on the use of Bukalapak, where there are still many complaints felt by Bukalapak users regarding long delivery, the Bukalapak help center cannot be contacted, and the pay later payment service is never late but the payment status is pending. These indications can be seen from user reviews published on several news sites. Sample determination was carried out through a purposive sampling technique. In this study, the sampling technique was carried out using the Slovin formula with an error tolerance level of 10%, so that the number of respondents was 100. Respondents were selected based on the criteria of having used Bukalapak e-commerce services for the last 5 months and being domiciled in Cirebon City. The data collection method was carried out by distributing questionnaires online via Google Forms. Path analysis technique using SPSS Version 29.0.2.0 for Windows. Hypothesis testing was carried out using the Sobel test method. The results showed that e-service quality has a positive and significant effect on e-trust, e-satisfaction, and e-loyalty. E-satisfaction and e-trust have a positive and significant effect on e-loyalty. The results of this study also show that e-satisfaction and e-trust can mediate the effect of e-service quality on e-loyalty. Keywords:  E-commerce, E-service quality, E-satisfaction, E-trust, E-loyalty